A Review of the Surface Roughness Prediction Methods in Finishing Machining - Trinh, Van-Long (Engineering, Technology & Applied Science Research, 2024)
The desired Surface Roughness (SR) can be achieved via general machining methods by using a cutting tool to remove a material layer on the workpiece surface. Cutting Parameters (CP), cutting tool properties, and workpiece properties must be considered. The finishing machining methods that can be applied to produce the desired SR are turning, milling, grinding, boring, and polishing. The technological parameters must be tightly combined in the Machining Process (MP). The CP selection presents some issues regarding time, cost, and practical skill when considering different cutting methods, cutting tools, and workpiece materials. SR predicting methods of machined parts have the advantages of shortening the time of CP selection, reducing machining cost, and bringing the desired SR. This paper reviews the recent methods followed in predicting the SR of the MPs. The SR prediction methods will bring many benefits for MP, such as improved SR, reduced cost, improved cutting conditions, and enhanced quality.